Loans From the European Stability Mechanism to Combat the Corona Crisis are Not Enough - Hans-Bernd Schäfer (Wirtschaftsdienst)
Abstract On 9 April 2020, the euro area finance ministers agreed on credit lines with the European Stability Mechanism (ESM) to counter the corona crisis. The ESM loans are estimated at 200 billion euros. However, this figure is misleading. Only a few states would benefit at all over a 10-year government bond in their own country. Moreover, the scope of ESM loans is limited.